They also do it: internet use by older adults living in residential care facilities - Seifert, Alexander; Doh, Michael; Wahl, Hans-Werner (Educational gerontology, 2017)
The Internet has gained much importance as a resource for older adults during recent years, for example, as a resource for maintaining lifelong learning. However, available studies targeting the adoption of the Internet have mostly focused on young-old, healthy, and community-dwelling adults. To our knowledge, no study has yet examined Internet use among individuals living in residential care facilities (RCF), that is, old-old adults with a range of functional impairments. We provide data on the Internet use in a large sample of 1,212 residents (mean age, 87.9 years) living in 24 RCFs in Zurich, Switzerland. We found that 14% of residents used the Internet, a very similar proportion as previously reported in a Swiss survey of older adults in private households. However, when stratified according to age, individuals aged 65-84 years in RCFs had lower Internet use compared with community-dwelling older adults (21% versus 65%, respectively). No difference was observed among individuals aged >85 years. Compared with non-users, Internet users were more likely to be younger, male, living for a shorter duration in RCF, not living alone in the institution, and healthier and functionally unimpaired. Internet users also described themselves as having higher autonomy and satisfaction with life. In conclusion, Internet use has reached (at least in Switzerland) the long-term care sector and appears to play a significant role in the lives of a considerable portion of RCF residents.